A Network Hierarchical Feedback System for Taiwanese Universities based on the Integration of Total Quality Management and Innovation - CHEN, I-SHUO (Elsevier, 2012)
An increasing number of Taiwanese universities are improving operational performance through innovation and total quality management (TQM). In addition, the National Quality Award (NQA), which is based on TQM, is now used to evaluate quality performance in various industries in Taiwan. Thus, several models for performance measurement have been proposed in recent years. However, these models do not take into account several features germane to performance within the Taiwanese university system, such as characteristics unique to the integration of TQM and innovation, comprehensive focuses in operational performance improvement across different types of universities, and interrelations among the different variables used to measure performance. Thus, precisely measuring and improving operation performance has proven to be a difficult task. The aim of this paper is to construct a network hierarchical feedback system (NHFS) based on the integration of TQM and innovation to overcome these problems. To that end, we adopted a decision-making trial and evaluation laboratory (DEMATEL) method to address the complex, interdependent relationships among the variables and thereby construct a relation structure among the measurement criteria for evaluation purposes. A fuzzy analytic network process (FANP) is employed to overcome the problem of dependence and feedback among each of the TQM measurement criteria. A fuzzy analytic hierarchical process (FAHP) is used to evaluate the measurement criteria for innovation performance. Lastly, a gray relational analysis (GRA) is utilized to find optimal alternatives. The value of this study comes from providing all types of universities in Taiwan the most complete evaluation system of operational performance, as well as opportunities to realize improved competitive advantages and enhanced prospects for survival.
IN_PRESS
Keywords: Education; Management; FAHP; FANP; total quality management; TQM; University Networks